The perspective of the level of understanding of islamic financial management based on intellectual intelligence - Nugroho, Anton Priyo; Alfiana, Alfiana; Mulatsih, Listiana Sri; Judijanto, Loso; Santoso, Aprih; Nusair, Ahmad Ershaid (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This study aims to determine the effect of intellectual intelligence on the level of understanding of Islamic financial management with interest in learning as a mediating variable in students of the Management Study Program, Faculty of Economics, University of Semarang. This study used primary data in the form of a questionnaire measured using a Likert scale. This study uses the census method. Data was obtained by distributing questionnaires to 97 students. Statistical method for testing the hypothesis using PLS. The results of testing the hypothesis show that intellectual intelligence and learning interest have a significant influence in a positive direction on the level of understanding of Islamic financial management in students of the Management Study Program, Faculty of Economics, University of Semarang. Interest in learning mam[u mediates the influence of intellectual intelligence on the level of understanding of Islamic financial management in undergraduate students of Management Faculty of Economics, University of Semarang.